Gandhian Spherons: India/Nepal Return to the Varnas Peace World Leadership - Pathak, Bishnu; Maguire, Mairead Corrigan; Avery, John Scales; Semashko, Mikhailovich Leo (Social Inquiry: Journal of Social Science Research, 2022)
The article summarizes 16 years of research by the Gandhian Global Harmony Association’s humanities scientists in the field of the genetic thermodynamic cybernetic social structure of nonviolence spherons and its empirical verification by world statistics. The article context narration is undertaken in the logic of theoretical knowledge, in the cognitive movement from the whole, general and abstract to the parts, single and concrete. This logic is accompanied and illustrated by a visual series of systemic structural modeling. The research of spherons as a deep invariant social structure that constitutes the genetic fundamental substance of any society in the corresponding innovative sociocybernetic science qualitatively changes the general traditional vision of society and raises its knowledge to the level of natural sciences with fundamentally new digital technologies in all its spheres. This qualitatively innovative science with Einstein’s "substantially new manner of thinking" based on the invariant genetic structure of spherons provides a single scientific, acceptable to all peoples, nonviolent solution of the civilizational confrontational crisis that began in 1914, since the WWI and continues to this day, together with all its aggravating and insoluble for traditional thinking global challenges, pathologies and pandemics. Only conscious, enlightened spherons are able to lead humanity out of the deadly dead end of more than a century global confrontation into the space of global convergence, sustainable development, solidarity and partnership. To continue and intensify these fundamental innovative scientific researches, it is proposed to create an independent International Humanitarian Academy of Spherons, for a start, from 20-30 humanities scientists, mathematicians, cyberneticians, statisticians and programmers in any country that agrees to finance it and which will pay for itself in 3-4 years.